Comparative Analysis of Governance Models Across Various Types and Sizes of Nonprofit Organizations - Deewan, Vinayak (Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement; Vol 1 No 1 (2025): Journal of Advanced Research in Nonprofit Organizational Governance and Social Impact Measurement, 2025)
This review article provides a comparative analysis of governance models employed by nonprofit organizations (NPOs) across various sizes and types. Nonprofits operate in diverse environments, and their governance structures must adapt to their mission, resources, and stakeholder needs. The article explores traditional, collaborative, policy governance, community-driven, and hybrid models, examining the strengths, challenges, and practical implications of each approach. By comparing these governance models across small, medium, and large organizations, the review highlights key factors that influence governance choices, including resource availability, mission scope, and stakeholder involvement. Understanding these differences is critical for nonprofits to effectively manage resources, ensure accountability, and achieve their social objectives. The findings emphasize the importance of aligning governance structures with organizational characteristics to enhance performance and long-term sustainability.